Reviving Values through Tradition: Integrating the Haul of KH. R. As’ad Syamsul Arifin into Character Education - Mahmudi, Mahmudi; Rizal, Alvin Noor Sahab (Mimbar Agama Budaya, 2025)
Character education is essential for shaping individuals with noble values, social responsibility, and integrity. This study explores how character values are embedded in the haul tradition, focusing on the Haul of KH. R. As'ad Syamsul Arifin at Pondok Pesantren Salafiyah-Syafi’iyah Sukorejo, Situbondo. Using a literature review method grounded in the anthropology of Islam, the research identifies key values such as exemplary behavior, humility, respect for scholars, social solidarity, and spiritual leadership within the haul. These values play a crucial role in character development. The study reveals that character education can be integrated into the community through adaptive strategies like hidden curriculum and intra-curricular and extracurricular activities. The results suggest that character education extends beyond formal classroom settings, flourishing through religious-cultural practices within the community, making the haul tradition a valuable model for culturally grounded character education.